True 2-D 5/3 wavelet transform and its application for CT image lossless compression - Nini XU; Mingming ZHANG; Jianming WANG (Dianxin kexue)
Wavelet transform is widely used in the field of digital image processing，and it usually processes image by separating the row and column，which can’t meet the human visual system（HVS）completely.To address this situation，a kind of true 2-D 5/3 wavelet transform was constructed，which was more consistent with HVS.Firstly，1-D 5/3 wavelet filter bank constructed the true 2-D Lazy wavelet filter bank by McClellan transform，and it was implemented by lifting scheme.Then，this lifting scheme was nested with the true 2-D Lazy wavelet filter bank to implement true 5/3 wavelet transform of image.To facilitate engineering applications，the transformation procedure was given.The experiments of true 5/3 wavelet transform used in CT image lossless compression，the experiment shows that，for 512×512 size CT image true 5/3 wavelet transform has better compression effect when compared with two dimensional separable 5/3 wavelet transform and can save 1 989.9 byte per piece on average.